1993
DOI: 10.1073/pnas.90.21.10345
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of learning, pain thresholds, and thermoregulation in the rat by preparations of free purified alpha-linolenic and linoleic acids: determination of the optimal omega 3-to-omega 6 ratio.

Abstract: Ingested polyunsaturated fatty acids are pos-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
1
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(85 citation statements)
references
References 42 publications
1
77
1
4
Order By: Relevance
“…Salem and Niebylski [106] proposed that DHA or (22:6, n-3) controls the level of cholesterol as well as the composition and function of the neuronal membrane. We recently reviewed a number of studies that provided support for reducing neuronal membrane cholesterol by dietary supplementation of an n-3/n-6 compound in a ratio of 1:4 [125]. It is possible that such a ratio optimizes uptake of PUFA into the brain and promotes fatty acid incorporation into the neuronal membranes.…”
Section: Cholesterol and Fatty Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Salem and Niebylski [106] proposed that DHA or (22:6, n-3) controls the level of cholesterol as well as the composition and function of the neuronal membrane. We recently reviewed a number of studies that provided support for reducing neuronal membrane cholesterol by dietary supplementation of an n-3/n-6 compound in a ratio of 1:4 [125]. It is possible that such a ratio optimizes uptake of PUFA into the brain and promotes fatty acid incorporation into the neuronal membranes.…”
Section: Cholesterol and Fatty Acidsmentioning
confidence: 99%
“…the need for a proper ratio between the essential fatty acids. We experimentally tested our hypothesis that the ratio of n-3 and n-6 may be a key factor in modulating behavioral and neuropharmacological effects of PUFA, and we then attempted to identify the optimal ratio [125]. To avoid the variations that occur in the composition of fatty acids in commercially prepared oils, and to exclude the possible confounding effects of other fatty acid or lipid admixtures, we used highly purified alpha-linolenic and linoleic acids.…”
Section: Specific Fatty Acid and The Ratio Between Various Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the tests we used evaluate only a subset of cognitive abilities, our results suggest that, at the least, the KD does not worsen visuospatial learning and memory or exploratory behavior. Although we have not tested cognitive or behavioral effects of other AEDs in this kindling model, both clinical and experimental studies raise questions about such adverse sequelae in other models (35)(36)(37) showed that rats fed a diet enriched in essential fatty acids having a high w3/w6 ratio performed better on the Morris water maze than did rats fed a standard diet or a diet with a lower w3/06 ratio (38). The KD contains a mixture of saturated and polyunsaturated fatty acids, and the prospect that a KD could be designed to optimize cognitive function warrants further investigation.…”
Section: Previous Animal Studies Using the Kdmentioning
confidence: 99%
“…Ainsi, un régime supplémenté en AGPI n-3 semble améliorer les performances dans le test discrimination visuelle [11] et dans le test de la piscine de Morris [13] déjà évoqués. Au vu de l'ensemble des résultats obtenus en cas de déficience et en cas de surcharge, on peut proposer l'existence d'une valeur « idéale » d'apport en AGPI n-3 ou de rapport AGPI n-6/n-3 pour des capacités cognitives optimales [20].…”
Section: Articleunclassified